Evaluation of Postoperative Radiotherapy Effect on Survival of Resected Stage III-N2 Non-small Cell Lung Cancer Patients - Gao, Fei; Li, Nan; Xu, YongMei; Yang, GuoWang (Frontiers in Oncology, 2020)
Objective: The role of postoperative radiotherapy (PORT) in resected Stage IIIA-N2 NSCLC patients remains controversial. This study is to explore the effect of PORT on survival of resected Stage IIIA-N2 NSCLC patients. Methods: Resected Stage IIIA-N2 NSCLC patients aged 18 years or older were identified from SEER database from 2010 to 2015. Cox regression analysis was used to identify factors including PORT associated with survival time. Subgroups analysis of patients stratified by number of lymph node metastases were also performed. Overall survival (OS) and overall mortality were compared among the different groups. Results: A total of 3445 patients were included in the study. Multivariate cox analysis showed PORT had no significant impact on survival of patients with < 6 positive lymph node (HR=1.012, P=0.858, 95% CI: 0.886-1.156). POCT (HR=0.605, P<0.001, 95% CI: 0.468-0.783) and PORT (HR=0.724, P=0.007, 95% CI: 0.574-0.914) are both favorable prognostic factors for stage IIIA-N2 patients with ≥6 positive lymph nodes. In 2735 patients featured < 6 number of positive regional lymph nodes, patients who received PORT had better survival and lower 3-year and 5-year overall mortality rate than patients who underwent surgery only(41 months vs 28 months，P < 0.015). There was no significant difference in the survival of postoperative patients who underwent POCT in view of whether received PORT(44 months vs 53 months，P = 0.176).710 patients featured ≥ 6 number of positive regional lymph nodes metastasis were divided into two groups by PORT. PORT did not prolonged survival for postoperative patients who did not receive chemotherapy (12 months vs 15 months，P = 0.632). PORT showed a significant advantage in influencing overall survival in patients received PORT combined with POCT compared with those who received POCT only(32 months vs 25 months，P = 0.006). Conclusions: For IIIA-N2 patients with < 6 lymph node metastases, PORT can be encouraged used to improve survival. For patients with ≥ 6 positive lymph nodes, PORT combined with POCT significantly improved OS and decreased overall mortality.